2005
DOI: 10.1038/sj.onc.1208863
|View full text |Cite
|
Sign up to set email alerts
|

Fate of UVB-induced p53 mutations in SKH-hr1 mouse skin after discontinuation of irradiation: relationship to skin cancer development

Abstract: Chronic exposure to ultraviolet (UV) radiation causes skin cancer in humans and mice. We have previously shown that in hairless SKH-hr1 mice, UVB-induced p53 mutations arise very early, well before tumor development. In this study, we investigated whether discontinuation of UVB exposure before the onset of skin tumors results in the disappearance of p53 mutations in the skin of hairless SKH-hr1 mice. Irradiation of mice at a dose of 2.5 kJ/m 2 three times a week for 8 weeks induced p53 mutations in the epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
(70 reference statements)
2
39
0
2
Order By: Relevance
“…Importantly, the chemopreventive effects of silibinin were lost in p53 +/− mice. We did not check for the loss of heterozygosity of the p53 +/− mice, but based on a previous study we can deduce that most of these mice had loss of heterozygosity by 8 weeks of chronic UVB radiation (32). These findings confirm that p53 plays an important role in the protective effects of silibinin against UVB-induced skin lesions and carcinogenesis.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, the chemopreventive effects of silibinin were lost in p53 +/− mice. We did not check for the loss of heterozygosity of the p53 +/− mice, but based on a previous study we can deduce that most of these mice had loss of heterozygosity by 8 weeks of chronic UVB radiation (32). These findings confirm that p53 plays an important role in the protective effects of silibinin against UVB-induced skin lesions and carcinogenesis.…”
Section: Discussionsupporting
confidence: 63%
“…5 To identify the early events that may contribute to the tumor development promoted by reduction of IKK␣ expression, we examined UVB-induced p53 V154A/R155C , p53 R270C , and p53 R275C signature mutations in the skin of mice irradiated for 2 weeks using PCR with mutation-specific primers. 8,29 The result showed that these p53 mutations occurred more frequently in Ikk␣ ϩ/Ϫ than in Ikk␣ ϩ/ϩ skin specimens (Figure 2A). However, most of the skin tumors, regardless of the genotype, were positive for these p53 mutations ( Figure 2B).…”
Section: Early Genetic Alteration: More Uvb-induced Signature P53 Mutmentioning
confidence: 88%
“…5,[27][28][29] The PCR primers used included the codons 154/155: 5Ј-CCTCCAGCTGG-GAGCCGTGCTT-3Ј (with mutant-specific sequences) and 5Ј-GAGGGCTTACCATCACCATC-3Ј; C to T mutations at codons 270 and 275: the forward mutant-specific sequences 5Ј-GGACGGGACAGCTTTGAGGTTT-3Ј and 5Ј-GTGTTTGTGCCTGCCT-3Ј, respectively, and the reverse sequences 5Ј-GCCTGCGTACCTCTCTTTGC-3Ј. The PCR primers for exon 5 of the p53 gene were 5Ј-TCTCTTCCAGTACTCTCCTC-3Ј and 5Ј-GAGGGCTTAC-CATCACCATC-3Ј.…”
Section: P53 Mutation Analysis Using Allele-specific Pcrmentioning
confidence: 99%
“…Studies have shown that UVB radiation produces a variety of adverse effects that includes DNA damage [14,15], mutations in key regulatory genes [16], inflammation [17,18], immuno-suppression [19,20], photo-aging and skin cancer [21,22]. UVB is directly absorbed by cellular DNA leading to the formation of DNA lesions primarily cyclobutane pyrimidine dimers and pyrimidine (6-4)-pyrimidone photoproducts [13,23].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%